Analysis of relative telomere length and apoptosis in humans exposed to ionising radiation - Ilyenko, I.; Lyaskivska, O.; Bazyka, D. (Experimental Oncology, 2011)
Background: Ionizing radiation could modify lymphocyte function via oxidative damage, DNA breaks, and resulting changes of proliferation, apoptosis and cellular senescence, where telomeres may play a critical role. Aim: To study the effect of low-dose irradiation on the telomere length and apoptosis rates in peripheral blood lymphocytes of irradiated persons. Patients and Methods: A study was performed on 83 peripheral blood samples from the Chornobyl clean-up workers, radiation workers exposed under the professional limits at construction works at the “Shelter” object and healthy controls. Bone marrow leukocyte telomere length was estimated in 15 patients with myelodysplastic syndrome secondary to low-dose radiation exposure and 12 age-standardized healthy donors. Relative telomere length was studied by the combination of a fluorescence hybridization in situ with PNA probe and flow cytometry, apoptosis — by Annexin-V test. Results: A significant relative telomere length decrease has been demonstrated in Chornobyl clean-up workers compared to healthy donors (13.2 ± 0.69 and 18.6 ± 0.73 respectively, p < 0.05), and a tendency (p < 0.1) in radiation workers. At doses over professional limits an inverse dependency is demonstrated between the relative telomere length and a number of lymphocytes in early stage of apoptosis. In MDS group a tendency of telomere elongation was demonstrated in bone marrow granulocytes in RAEB-t and RAEB as comparing with RA. Conclusion: This study shows telomere shortening after low-dose irradiation and preservation of these changes even 20 years after exposure. Apoptosis induction is possible by the telomere region changes at least in individuals with shorter telomeres. Apoptosis decrease in MDS clonal transformation is associated with a substantially longer telomeres.